Detecção molecular de herpesvírus bovino tipo-1 e herpesvírus bovino tipo-5 em amostras de encéfalos bovinos incluídos em parafina - Silva, Danilo Rezende e (2014)
Identification of herpesvirus in specimes fixed in formalin and paraffin embedded has been used in experimental analysis. Several molecular techniques have been used in research and in diagnosing of herpesviral meningoencephalitis. 80 cases of routine in veterinary pathology were reviewed on the Department of Animal Pathology of Veterinary and Science Animal School Medicine of Federal University of Goias, Goiania, GO (EVZ/UFG) performed between January 2007 to December 2012. Were used 18 cases with a total of 44 paraffin blocks (Group I - 14 blocks, Group II - 17 blocks and Group III - 13 blocks), which were grouped according to histopathological diagnosis, in Group I - samples without histological changes and no clinical history of neurological disease, Group II - samples with nonspecific encephalitis, Group III - samples with rabies encephalitis. Were extracted DNA fragments, from cuts blocks, using a commercial extraction kit of formalin and paraffin embedded tissue. Afterwards the technique standardization of conventional PCR for bovine herpesvirus-1 and bovine herpersvírus type-5 was performed. Were positive for BoHV-5 28% (5/18) of cases, with 11% (2/18) of the group with nonspecific encephalitis and 17% (3/18) of the group with encephalitis and positive for the rabies virus. In the test for checking of the bands for the BoHV-1, all samples, 100% (18/18) were negative. These results demonstrate that the conventional PCR technique is helpful in aiding the definitive diagnosis of encephalitis bovine herpesvirus type-5.